Post militancy Tourism in Swat: Perceptions of Tourists from Malakand Division, Khyber Pakhtunkhwa, Pakistan - Naila Alam (Journal of Peace, Development and Communication, 2022)
Tourism is a temporary but multi-facet journey. It is visible across the globe and more frequent in develop world where tourism is encouraged and professionally developed at national level. Pakistan is located in South Asia, where tourism is observed in all provinces including Khyber Pakhtunkhwa (KP). The current study was conducted in 2021 to record the status of tourism in Swat after post militancy. This was a mix study method, however mainly focused on qualitative approach. After 2007 militancy in Swat, tourism industry suffered a lot. The study aimed to explore the status of tourism in Swat in view of tourists’ perceptions. The study also investigated the satisfaction of tourists in view of restored peace and safety after armed forces operation against militancy. Quantitative data were collected via questionnaire. Qualitative data was recorded via A total of 400 tourists visited different tourist spots of Malakand, Swat, Dir, Chitral, Shangla and Bunir districts of Malakand Division. There were recorded 180 tourists visiting Swat. Convenience sampling was used. Data was processed thematically. The study confirmed restoration of peace and safety after armed forces action against militancy in Swat. Tourists were feeling no more insecure to visit Swat. A proper attention is required to develop tourism industry for economic benefit and further projecting the healthy image of Pakistan at international level. A special attention of the policy-makers is invited in this context.